Genetic control of seasonal meristem arrest in trees - Jun Wang; Xiaoli Liao; Zhihao Wu; Shashank Sane; Shaopeng Han; Qihui Chen; Xueping Shi; Xiaokang Dai; Maria Klintenäs; Ove Nilsson; Jihua Ding (Proceedings of the National Academy of Sciences, 2025)
Perennial plants, such as trees native to temperate and boreal regions, exhibit meristems that undergo annual cycles of activity and rest to synchronize their growth cycles with seasonal changes, ensuring survival under harsh winter conditions. The arrest of shoot meristem growth, known as growth cessation, is a critical initial step for trees to enter dormancy. This process is triggered by a combination of endogenous and exogenous signals, yet the molecular mechanisms and signaling pathways underlying growth cessation remain poorly understood. In this study, we demonstrate that Populus orthologs of APETALA2-like transcription factors (AP2Ls), the primary regulators of global proliferative arrest (GPA) in Arabidopsis , play a crucial role in the regulation of seasonal growth cessation in hybrid aspen trees. In particular, AP2Ls act as important activators of the expression of FLOWERING LOCUS T2 ( FT2 ), a key gene for short-day-induced growth cessation. This contrasts with the established role of AP2Ls as repressors of FT in annual plants. Yet, the pathway itself is conserved with the pathway regulating GPA in annual plants, a completely different process during the plant life cycle. Our research highlights both the conserved roles and functional diversities of AP2Ls in a more general balancing of meristem proliferation and arrest in perennial plants, providing insights into the evolutionary adaptation of growth regulation mechanisms across plant species.